Inkdeath - Funke, Cornelia Caroline (Chicken House, 2008)
As Bluejay--Mo's fictitious double--tries to keep the Book of Immortality from unraveling, Adderhead kidnaps all the children in the kingdom, asking for Bluejay's surrender or the children will be doomed to slavery in the silver mines